PENENTUAN MODEL SISTEM ANTREAN KENDARAAN DI GERBANG TOL BANYUMANIK SEMARANG - Dedi Nugraha; Sugito Sugito; Dwi Ispriyanti (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2013)
The arrival rate of vehicles that have occured at the Banyumanik tollgate is randomly and fluctuatly. Those condition would make difficult for tollgate management to determine policies in operating the substation service. If the substation service operates slightly, can occur long queues, especially at certain time. In the meantime, if the substation service operates many service, service to be inefficient. Therefore, it is necessary to determine the queuing system model in accordance with the conditions and characteristics of the queue from service facilities at the Banyumanik tollgate appropriately. So it can be determined the efektif and efisien number of service substation. Based on the analysis of data obtained, a queue model system that occurred at the Banyumanik tollgate is . The efektif number of substations service for directions Ungaran-Semarang are two subtations service. While for direction Semarang-Ungaran, the efektif number of substation service is three.